Twenty-two new Asian short stories - Quayum, Mohammad Abdul (Silverfish Books, 2016)
An excerpt from the introduction ... twenty-two stories in the volume, and this is how the tally stands country-wise: one each from Bangladesh, Hong Kong, Malaysia, Nepal and Pakistan; four from the Philippines, five from Singapore and eight from India. In this count, I have considered only the country of origin of the authors, because some of them have moved either to another country within Asia or to the West ... if we leave out the internal migrations within the continent, there are only three writers in this volume, who are based in the West, compared to ten in the previous volume which prompted one reviewer, renowned Bangladeshi poet Kaiser Haq, to ask half-humorously if the whole of Asia was in exile. “A Continent in Exile?” was the title of his review of A Rainbow Feast.